The effect of resveratrol on oxidative stress in the liver and serum of a rat model of polycystic ovary syndrome: An experimental study - Mahnaz Ghowsi; Homayoun Khazali; Sajjad Sisakhtnezhad (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Studies of oxidative status in polycystic ovarian syndrome (PCOS) patients are limited with inconsistent results. The effects of resveratrol as a natural antioxidant on oxidative status in PCOS aren’t clear. Objective: This study evaluated effects of resveratrol on oxidative stress in the liver and serum of the PCOS rats. Materials and Methods: Fifteen female Wistar rats (3 wk old) were divided into 3 groups (n=5/each e): Control group, PCO-Control group, and PCO-Resveratrol group. For induction of polycystic ovary phenotype, testosterone enanthate 10 mg/kg was injected for 35 days subcutaneously. Then, resveratrol 10 mg/kg was injected intraperitoneally for 28 days to rats of the PCO-Resveratrol group. Ovarian sections were stained with hematoxylin/eosin. The serum glucose and insulin and the levels of malondialdehyde (MDA) and total antioxidant capacity (TAC) in serum and liver were measured. Results: Control animals showed normal ovarian morphology and PCO-Control animals exhibited cystic follicles. There were no significant differences in liver TAC between groups. The serum MDA (p=0.034), and homeostatic model assessment insulin resistance (HOMA-IR) (p=0.014) levels in PCO-Control rats were higher than the controls. The liver MDA in PCO-Control rats was more than that of controls (p=0.001). The HOMA-IR (p=0.008) and serum MDA (p=0.006) levels in PCO-Control rats were more than those of PCO-Resveratrol rats (p=0.008). In PCO-Resveratrol group, serum TAC was higher than that of PCO-Control group (p=0.022) and liver MDA was more than controls (p=0.01). Conclusion: Results indicated that the induction of PCOS in rats increased lipid peroxidation and insulin resistance and resveratrol improved these complications.